MAINTENANCE ANALYSIS OF SWD 1 MACHINE USING RELIABILITY CENTERED MAINTENANCE (RCM) METHOD AT PLTD TELLO - Padhil, Ahmad; Mail, Abdul; Jannah, Miftahul (LPPM-ITEBA, 2023)
PT PLN (Persero) is one of the companies tasked with implementing government policies in the field of services, provision and utilization of electricity, as well as supporting electricity businesses to the public. Diesel Power Plant (PLTD) is a power plant that uses a diesel engine as the prime mover, the engine as the prime mover, which functions to produce the mechanical energy needed to rotate the generator rotor to produce electricity. The SWD 1 engine at PLTD Tello has experienced several cases of problems that have an impact on the required electricity production. The purpose of this study is to determine the maintenance interval schedule for Werkspoor Diesel (SWD 1) on critical components that often experience damage, and determine the right maintenance strategy for these critical components. This research uses the Reliability Centered Maintenance (RCM) method. The results of this study are a maintenance interval schedule based on a reliability centered maintenance (RCM) approach for critical components that experience failures, namely Cylinder Head with preventive maintenance intervals every 34.66 hours or every 4 times a day set on Monday and Thursday. And the strategy to reduce damage to the SWD 1 unit based on the Reliability Centered Maintenance (RCM) approach regarding SWD 1 engine maintenance uses a preventive maintenance strategy where preventive maintenance is carried out in accordance with the schedule, then corrective maintenance or component replacement if it is seen that the condition is urgent to replace.